DETERMINATION OF TRACE AND TOXIC ELEMENTS IN FOUR PAKISTANI BARLEY (HORDEUM VULGARE L.) VARIETIES AND ITS SOIL COLLECTED FROM PIRSABAK (NWFP), PAKISTAN - Shar, G. Q.; Shar, L. A.; Kazi, T. G.; Afridi, H. I.; Arain, M. B.; Jamali, M. K. (Journal of Research (Science), 2007)
A study was conducted to determine the concentration of trace and toxic metal accumulation in barley varieties and soil grown at Cereal Crop Research Institute (CCRI), Faisalabad using flame atomic absorption spectrophotometer. In this connection wet ashing method used to destroy the organic matrix. The highest level in (mg/kg) of trace and toxic metals determined in barley varieties and its soil were found 5.75-7.57 (Cu), 3.21 – 3.79 (Co), 0.75 – 1.13 (Cr), 1.68 – 5.67 (Ni), 2.19 – 6.76 (Ba), 16.71 – 29.28 (Al), 1.01 – 1.46 (Pb) and 0.18 – 0.44 (Cd). The concentration in (mg kg-1) of the soil of that specific plot was observed 14.74 ± 1.39 (Cu), 6.07 ± 0.81 (Co), 7.09 ± 0.65 (Cr), 8.39 ± 1.29 (Ni), 116.74 ± 8.02 (Ba), 18821.4 ±1583.8 (Al), 3.88 ± 0.45 (Pb) and 1.25 ± 0.16 (Cd). Using reference material checked the validity of digestion method.